MDS-associated mutations in germline GATA2 mutated patients with hematologic manifestations. (January 2019) - McReynolds, Lisa J.; Yang, Yanqin; Yuen Wong, Hong; Tang, Jingrong; Zhang, Yubo; Mulé, Matthew P.; Daub, Janine; Palmer, Cindy; Foruraghi, Ladan; Liu, Qingguo; Zhu, Jun; Wang, Weixin; et al.
Highlights: We describe "GATA2 deficiency related bone marrow and immunodeficiency disorder" (G2BMID). G2BMID patients have hypocellular BM with no definitive dysplasia and with cytopenia. G2BMID patients have clonal hematopoiesis with detectable MDS-associated mutations. Abstract: Germline mutation in GATA2 can lead to GATA2 deficiency characterized by a complex multi-system disorder that can present with many manifestations including variable cytopenias, bone marrow failure, myelodysplastic syndrome/acute myeloid leukemia (MDS/AML), and severe immunodeficiency. Penetrance and expressivity within families is often variable. There is a spectrum of bone marrow disease in symptomatic cytopenic patients ranging from hypocellular marrows without overt dysplasia to those with definitive MDS, AML, or chronic myelomonocytic leukemia. Relatives of probands with the same mutations may demonstrate minimal disease manifestations and normal marrows. A comprehensive clinical, hematological and genetic assessment of 25 patients with germline GATA2 mutation was performed. MDS-associated mutations were identified in symptomatic GATA2 patients both with overt MDS and in those with hypocellular/aplastic bone marrows without definitive dysplasia. Healthy relatives of probands harboring the same germline GATA2 mutations had essentially normal marrows that were overall devoid of MDS-associated mutations. The findings suggest that abnormal clonal hematopoiesis is a common event in symptomatic germline mutated GATA2 patients with MDS and also in those with hypocellular marrows without overt morphologic evidence of dysplasia, possibly indicating a pre-MDS stage warranting close monitoring for disease progression.